Research and evaluation on students’ emotional attachment to campus landscape renewal coupling emotional attachment scale and public sentiment analysis: a case study of the “Heart of Forest” in Beijing Forestry University - Zhang, Ruoshi (Frontiers in Psychology, 2023)
In the era of stock renewal, the construction of university campuses in China's first-tier cities has shifted from demolition and construction to renewal and upgrading, in which public landscape space is the main environment for students' daily life, learning and entertainment. Especially during the outbreak of the recent COVID-19 epidemic, it has become an important way for students to interact with nature and obtain emotional healing. In the existing studies, there is a lack of discussion on the correlation between the spatial characteristics of the updated campus landscape and students' emotional attachment, and there are few quantitative studies. Based on this, this paper takes the "Heart of Forest" landscape space as an example, and integrates multi-dimensional quantitative methods including emotional attachment scale and public semantic analysis to study and evaluate the characteristics of landscape space that affect students' emotional attachment. The results show that: (1) Overall, the landscape space renewal of the Heart of Forest provides students with positive emotional experiences and effectively enhances students' emotional attachment as well as sense of belonging to the campus. (2) Among them, the material characteristics of the site including nature-related elements, materials, structures play a positive role in promoting the vast majority of students in the process of establishing emotional attachment, which is particularly obvious for students majoring in landscape, architecture and urban planning. (3) Whether the public social space can effectively provide students with a good emotional experience is closely related to the frequency and purpose of students' use of the space. (4) The interactive characteristics such as changeability and playability fail to promote emotional attachment because of lacking of management and maintenance. The renewal and transformation of the "Heart of Forest" landscape space is generally successful in promoting students' emotional attachment, and provides a reference for the future campus landscape renewal design from different angles. In addition, the quantitative study of emotional attachment constructed in this paper coupled with multidimensional data provides a method for the evaluation of students' emotional experience of campus landscape.